2014
DOI: 10.1007/s11051-014-2629-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effective density of airborne nanoparticles using multiple charging correction in a tandem DMA/ELPI setup

Abstract: Increasing numbers of workers are exposed to airborne nanoparticles, the health effects of which remain difficult to evaluate. Effective density is considered to be a key characteristic of airborne nanoparticles due to its role in particle deposition in the human respiratory tract and in the conversion of number distributions to mass distributions. Because effective density cannot be measured directly, in this study the electrical mobility and aerodynamic equivalent diameters of airborne nanoparticles were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The size-resolved MAC was calculated using the Mie scattering model (Bohren and Huffman, 2007). Based on the Mie scattering theory, MAC values vary for different aerosol core diameter and different total diameter.…”
Section: Transform the Size-resolved σ Abs Into Bcmsdmentioning
confidence: 99%
“…The size-resolved MAC was calculated using the Mie scattering model (Bohren and Huffman, 2007). Based on the Mie scattering theory, MAC values vary for different aerosol core diameter and different total diameter.…”
Section: Transform the Size-resolved σ Abs Into Bcmsdmentioning
confidence: 99%
“…A given electrical mobility diameter was selected from a polydisperse aerosol of DEHS droplets (AGK 2000, Palas), using a DMA Vienna Type selector (Grimm, Q sheath D 3 L/min, Q aerosol D 0.3 L/min). Assuming that the proportion of multiply charged particles was negligible (see, e.g., Bau et al 2012), this results in the production of monodisperse aerosols with a given electrical mobility diameter, and a corresponding geometric standard deviation typically smaller than 1.05, as described in previous studies where a model for the DMA transfer function was applied (Bau et al 2014). Ten aerodynamic diameter values between 0.14 and 0.95 mm were used in this series of experiments.…”
Section: Test Rig For the Generation Of Monodisperse Submicronic Aeromentioning
confidence: 99%
“…Therefore, mass distribution and particle density play pivotal roles in the study of associated health effects. However, obtaining measurements of the morphology or density of aerosol particles in the environment is not easy (Bau et al, 2014;De-Carlo et al, 2004), and particles in an ambient environment are generally irregular and nonspherical. In this regard, Liu et al (2013) demonstrated that the morphological parameter of a fractal soot particle, namely the fractal dimension (D f ), could affect the particle's radiative properties.…”
Section: Introductionmentioning
confidence: 99%